Cosmological Models of the Universe - An Overview - Paul, Dilip (New Frontiers in Physical Science Research Vol. 2, 2022)
A cosmological model is a mathematical description of the observed universe which is concerned with the fundamental queries on creation, evolution, large scale structure formation of the universe. The standard cosmological model is based on Einstein’s General theory of Relativity with perfect fluid assumption. A large number of cosmological models in the context of ever changing fundamental theory have been proposed during the last few decades. This article contains a brief review of these models especially Big Bang model and Inflationary model of the universe.